DETERMINANTS OF SALES PERSON PERFORMANCE - Noor, Naseer; Ramayah, T.; Wahabi, Mohd. Ameen SMA Abdul (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2001)
This study examines the relationship between aptitude, skill level, role perception and personal factors toward salesperson performance. The bulk of the earlier research has been conducted in the developed countries, mostly American environment. A sample of 103 respondents were used in this study. The three independent variables investigated, all of them, skill/ role perception, aptitude and personal factors turned out to be significantly related to the salesperson performance. Skill/role perception is found to be the most important variable in explaining the variance in salesperson performance. The results of this study would enhance the understanding of the determinants of salesperson performance for organizations in Malaysia which could be used as a guide line to increase their salespersons’ performance. At the same time, it is also hoped that this study will encourage further marketing studies that are still comparatively lacking in Malaysia.